Impact of paddy growth stages on the parasitoid community of yellow stem borer (Scirpophaga incertulas) - PRASANTHI, GOLIVE; DEY, DEBJANI; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2020)
The yellow stem borer (YSB) (Scirpophaga incertulas) (Pyralidae: Lepidoptera) is a conundrum pest of paddy in India. One of the best ways to overcome the attack of this pest is to control the initial stage of its life cycle by parasitoids. Per cent infestation of yellow stem borer and extent of parasitization was assessed in organic and conventional paddy fields at ICAR-Indian Agricultural Research Institute, New Delhi. Results revealed that stem borer infestation was more (0.59%) in conventional rice than organic rice (0.47%). Larval parasitoids, viz., Myosoma chinensis (Szepligeti), Trathala flavoorbitalis, Temelucha philippinensis and pupal parasitoids Xanthopimpla punctata emerged from both conventional and organic cropping systems. Myosoma chinensis was the most dominant among all the parasitoids recorded and all are new records to Delhi region. This study indicated that organic cultivation practices supported more to beneficial insects. Overall per cent parasitization under organic ecosystem was higher (34.6%) to conventional ecosystem (13.3%).